Molecular characterization of the thermostability and carbohydrate-binding module from a newly identified GH118 family agarase, AgaXa. (January 2017) - Wu, Yi-Rui; Zhou, Zheng-Rong; Zhao, Min; Lin, Bokun; Zhong, Mingqi; Hu, Zhong
Graphical abstract: Highlights: AgaXa mutants were generated via the random and site-directed mutagenesis. The crucial amino acids related to thermostability and enzymatic activity were demonstrated. The location of carbohydrate-binding site was identified from the truncated mutants of AgaXa. Molecular mechanism of this new agarase member in GH118 family was firstly investigated. Abstract: AgaXa is a thermostable β-agarase from the agar-degrading bacterium Catenovulum sp. X3. To further understand the mechanism of protein stabilization of AgaXa, several mutants were generated by random and site-directed mutagenesis, and they were subsequently screened by analysing their enzymatic activity and thermostability. Four mutants (V197D, P259H, C442S and C528S) were found for which the enzyme activity and thermostability were significantly decreased. Moreover, secondary structures determined by circular dichroism (CD) showed that mutants V197D and P259H presented a higher percentage of α-helix but fewer β-strands than wild-type (WT) AgaXa. On the contrary, no significant changes were observed in the secondary structures of mutants C442S and C528S. Through the treatment by proteinase K, different digested profiles were generated from mutants V197D and P259H when compared to WT, and mutants C442S and C528S was observed with more digested protein fragments. These results indicate that the enzymatic activity and stability of AgaXa is mainly related to its hydrophobic structure and disulphide bonds. Furthermore, carbohydrate-binding ability was also analysed for the mutants of N- and C-terminal deletions, and the results showed that agarose binding capability was not changed, indicating that the carbohydrate-binding module is probably located in the middle of the β-agarase AgaXa.